Synthesis, Characterization and Thermal Behaviour of Solid 2-Methoxycinnamylidenepyruvate of Light Trivalent Lanthanides - Carvalho, C. T. [UNESP] (2009)
Solid state Ln-2-MeO-CP compounds, where Ln stands for light trivalent lanthanides (La, Ce, Pr, Nd, Sm, Eu, Gd) and 2-MeO-CP is 2-methoxycinnamylidenepyruvate, were synthesized in this work. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, experimental and theoretical infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information regarding the composition and stability of the isolated complexes.